Greenhouse gas abatement strategies and costs in French dairy production. (1st November 2019) - Mosnier, Claire; Britz, Wolfgang; Julliere, Thomas; De Cara, Stéphane; Jayet, Pierre-Alain; Havlík, Petr; Frank, Stefan; Mosnier, Aline
Abstract: The French dairy sector—like the rest of the economy—has to address the challenge of mitigating greenhouse gas (GHG) emissions to curb climate change. Deciding the economically optimal mitigation level and mix of abatement strategies requires knowledge on the cost of reducing GHG emissions. Agricultural bio-economic models can help identify which production-system changes are needed to reduce GHG emissions at different levels of incentives at minimal cost. The results reflect the model structure and parameter set, especially for GHG emissions accounting. Here abatement strategies and related costs for several levels of tax on GHG emissions in French dairy production are compared using four bio-economic models: the three supply models AROPAj, ORFEE and FARMDYN and the global partial equilibrium model GLOBIOM. It is found that between 1% and 6% GHG emissions abatement can be achieved at the current price of the EU allowances without substantially reducing milk production or outsourcing input production such as feed or herd renewal. Cost estimates reflect the planning horizon: mitigation is more expensive when past investments are not amortized. Models that account for demand-side factors show that a carbon tax has potential negative impacts on consumers through higher milk prices, while these price increases partly offset the reductionsin farm income. Model results suggest that promising on-farm GHG emissions abatement strategies include measures that let animals reach their full production potential and moderately intensive land management. Highlights: GHG abatements simulated by three supply farm models and one partial equilibrium model. 15% milk price increase and considerable decrease in profits found at 100€/tCO2 eq tax. 1%–6% and 4%–15% abatement found at 20€ and 100€ tax with limited outsourcing. Up to 70% GHG abatement found at 100€/tCO2 eq tax if the carbon tax is not embodied in trade. Up to 15% GHG abatement found with productive dairy cows raised on low-input forages.